BINARY MODEL OF THE RADIO ENGINEERING SYSTEMS OBJECTIVE FUNCTION. - Ivanov, Oleksandr; Kozlovska, Diana; Yevsiuk, Mykola; Melnyk, Yaroslav (Science-based technologies, 2024)
The problem of determining the rational composition of complex radio engineering structures belongs to the class of optimization problems, most of which do not have standard solutions and require the use of specialized algorithms for finding solutions. The complexity of mathematical analysis, stability analysis and optimal solution requires the use of numerical methods, as well as the use of methods for checking the independence of the objective function and connection functions, for example, checking functions for convexity to determine the unimodality of the problem. An approach to the study of target functions of radio engineering systems in the form of two-alternative binary functions is proposed. This approach allows us to determine the goal of the system, presented in the form of a three-level hierarchical structure, which is achieved in the case when the input influences and the reliability of their fixation correspond to predetermined limits. The concept of a three-level system of system engineering functions as an object of synthesis is formed. The normalized functions of the input influences of individual subsystems and the assessment of the reliability of the response of the system as a whole are determined. The objective function of the system formed at the upper level is shown. The proposed model of target functions takes into account compliance with the norm of all physical influences, regardless of their nature. The purpose of using the proposed approach is to determine the optimal parameters of the designed system, which vary in a given area of limitations, at which the maximum (or minimum) of the objective function is achieved (that is, the optimization of the objective function is carried out).